Ecological GDP Reform through Regenerative Macroeconomics: A Systematic Review of Theoretical Paradigms - Wibowo, Maulana Agung; Achsani, Noer Azam; Winoto, Joyo; Justianto, Agus (Journal of Environmental Accounting and Management, 2026)
Despite growing interest in ecological economics, no unified framework currently bridges normative critiques with operational fiscal reform. Existing macroeconomic systems frequently exclude ecological dynamics from accounting, limiting their capacity to reflect interdependence and regenerative processes. While sustainability paradigms aim to maintain ecological thresholds, their institutional integration often remains partial. In contrast, regenerative approaches embed restoration obligations, ecological productivity, and feedback loops as productive functions within macroeconomic systems. This study reviews 388 peer-reviewed articles to develop a regenerative macroeconomic model that embeds ecological values into national accounting. Using PRISMA-SLR, entropy-based coding, and PLS-SEM, the model formalises ecosystem contributions, restoration obligations, and fiscal redistribution. Results demonstrate that implementation actors exert more substantial influence on outcomes than institutional structures, with limited support for theory-driven pathways. The proposed framework provides a reproducible and policy-relevant tool that advances ecological macroeconomics by aligning fiscal systems with regenerative thresholds and positioning nature as a co-producing institutional actor.